Critical perspectives on diversity, equity, and inclusion in marketing - Gbadamosi, Ayantunji (Business Science Reference, 2022)
"This book covers the fields of Marketing, Ethics, and Diversity to provide the resources necessary for researchers, managers, and policy makers for insight into consumption practices, diversity, inclusion, limitations, and their theoretical and practical implications"--